'Building the Global Network?' The Reform of the Foreign and Commonwealth Office under New Labour. (19th September 2012) - Hall, Ian
<x xml:space="preserve">Abstract</x> From 1997 onwards the FCO was reshaped by New Labour. The removal of responsibility for overseas aid to a new Department of International Development (DFID) was perhaps the most dramatic change. Successive cuts to the FCO budget and the progressive centralization of foreign‐policy decision‐making in Number 10 also had their effects, as did a series of government‐directed reforms to recruitment practices. In an effort to make it more accountable to the public, the FCO was also bound by Public Service Agreements specifying targets for service delivery, publish Strategy Reports and mission statements, and Annual Departmental Reports setting benchmarks for performance. Together these reforms were designed to transform the FCO's culture, replacing inherited traditions of thought and practice with new ones believed better suited to contemporary world politics. This paper examines these inherited and new traditions, as well as the dilemmas they addressed.